Elevated serum levels of anti‐Müllerian hormone can be introduced as a new diagnostic marker for polycystic ovary syndrome. (15th October 2013) - Sahmay, Sezai; Atakul, Nil; Aydogan, Begüm; Aydın, Yavuz; Imamoglu, Metehan; Seyisoglu, Hakan
Abstract Objective To determine the possible role of anti‐Müllerian hormone (AMH) in the diagnosis of polycystic ovary syndrome (PCOS) with a larger population of women and to evaluate its role as a new diagnostic marker. Design Cross‐sectional study. Setting University hospital. Population A total of 570 women, with PCOS (n = 419) and without PCOS (n = 151). Methods Serum basal hormone; AMH, follicle stimulating hormone (FSH), luteinizing hormone (LH), prolactin, and thyroid‐stimulating hormone (TSH) levels were measured. Mean hormone levels were compared and the predictive value of serum AMH level was evaluated with the use of the receiver operating characteristic (ROC) curve analysis. Results No statistically significant differences were found between PCOS women and control groups in terms of age, body mass index and TSH levels. Differences between mean serum, FSH, LH and estradiol levels and LH/FSH ratio were found to be statistically significant (p < 0.001). Mean serum AMH level was higher in PCOS women than in controls (7.34 vs. 2.24 ng/mL, p < 0.001). The area under the ROC curve assay yielded a satisfactory result of 0.916 (95% confidence interval 0.897–0.935, p < 0.0001). The best compromise between 89.8% specificity and 80% sensitivity was obtained with a cut‐off value of 3.94 ng/mL for PCOS diagnosis. Conclusions Serum AMH measurement is very valuable in the diagnosis of PCOS women. The serum AMH level in women with hyperandrogenism or oligo‐anovulation could indicate the diagnosis of PCOS when reliable ultrasonography data are not available or when typical clinical and laboratory findings are not available. The serum AMH level is a new and useful diagnostic tool in PCOS diagnosis.